Cytoskeletal Proteins and Platelet Signaling - Fox, Joan E. B. (Thrombosis and Haemostasis, 2001)
The actin filament network fills the cytoplasm of unstimulated platelets and connects with a submembranous latticework of short cross-linked actin filaments, known as the membrane skeleton. One function of the cytoskeleton is to direct the contours of the membrane in the unstimulated platelet and the rapid changes in shape in the activated platelet. Activation-induced changes result from events such as phosphorylation or calpain-induced cleavage of cytoskeletal proteins. The specific reorganizations depend upon the combination of signals to which platelets are exposed. A second function of the cytoskeleton is to bind other cellular components; it binds signaling molecules, localizing them to specific cellular locations; it binds the plasma membrane regulating properties of the membrane, maintaining microdomains in the membrane, or regulating activities of membrane proteins. In this way, the cytoskeleton plays a critical role in regulation of spatial organizations and, thus, in the integration of cellular activities.
Keywords: Cytoskeleton; signaling; platelet shape; spatial organizations